FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KECEMASAN PASIEN DI IGD RS BHAYANGKARA MANADO - Mastur, Vergeina Ayu Mandalike; Villia E.G.J. Kani (Yayasan Syalom Cipta Sumikolah, 2025)
The number of sufferers of anxiety disorders reaches 5% of the world's population. The ratio of sufferers of anxiety disorders in women and men is 2 to 1. It is estimated that 2% -4% of the world's population have experienced anxiety disorders. The prevalence of anxiety disorders in Uganda, Africa obtained results of 26.6% with women higher than men, namely 29.7% in women and 23.1% in men. One of the factors that can reduce the patient's anxiety level is by providing therapeutic communication. Family support also affects anxiety levels, family support is very important for someone to focus on treatment and recovery. The goal is to find out the factors associated with the level of anxiety. This research uses quantitative with a descriptive analytic research design with a cross-sectional approach. The population is 250 patients with a sample of 71 respondents.The results of the nurse's Therapeutic Communication Factors in the Emergency Room at Bhayangkara Hospital Manado, namely Therapeutic Communication with the Good category 45 (63.4%). Family Support Factors in the Emergency Room at Bhayangkara Hospital in Manado, namely Family Support with a Poor Category 38 (53.5%). The level of anxiety in the Emergency Room at the Bhayangkara Hospital in Manado, namely the level of anxiety in the mild category, is 32 (45.1%). The results of statistical tests using the chi-square test obtained n P-value: 0.005 less than the value of α = 0.05, there was a relationship between the therapeutic communication factor of nurses and the patient's anxiety level at the Emergency Room at Bhayangkara Hospital, Manado. The results of statistical tests using the chi-square test obtained a P-value: 0.004 which is less than the value of α = 0.05. There is a relationship between family support factors and patient anxiety levels at the Bhayangkara Hospital Emergency Room, Manado